Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the roots of the polynomial equation [tex]\(x^4 + x^3 = 4x^2 + 4x\)[/tex], we will systematically solve it step by step.
1. Rewrite the equation:
Start with the given polynomial equation:
[tex]\[ x^4 + x^3 = 4x^2 + 4x \][/tex]
2. Bring all terms to one side:
To facilitate solving, we move all terms to one side of the equation:
[tex]\[ x^4 + x^3 - 4x^2 - 4x = 0 \][/tex]
3. Factor the polynomial:
To solve for [tex]\( x \)[/tex], we can try to factor the polynomial. Notice that all terms have a common factor, which is [tex]\( x \)[/tex]:
[tex]\[ x(x^3 + x^2 - 4x - 4) = 0 \][/tex]
This gives us one root directly:
[tex]\[ x = 0 \][/tex]
4. Solve the remaining polynomial:
Now, we need to solve the cubic equation:
[tex]\[ x^3 + x^2 - 4x - 4 = 0 \][/tex]
Through further factoring or using methods such as the Rational Root Theorem, we can find that the factors of this polynomial include [tex]\( (x + 2) \)[/tex], [tex]\( (x + 1) \)[/tex], and [tex]\( (x - 2) \)[/tex].
This means we can write:
[tex]\[ x^3 + x^2 - 4x - 4 = (x + 2)(x + 1)(x - 2) \][/tex]
5. Find the remaining roots:
Solve for [tex]\( x \)[/tex] from the factored form:
[tex]\[ (x + 2) = 0 \quad \Rightarrow \quad x = -2 \][/tex]
[tex]\[ (x + 1) = 0 \quad \Rightarrow \quad x = -1 \][/tex]
[tex]\[ (x - 2) = 0 \quad \Rightarrow \quad x = 2 \][/tex]
6. Collect all roots:
Combining these solutions, we get the roots of the polynomial equation [tex]\( x^4 + x^3 = 4x^2 + 4x \)[/tex]:
[tex]\[ x = -2, -1, 0, 2 \][/tex]
Therefore, the roots of the given equation [tex]\( x^4 + x^3 = 4x^2 + 4x \)[/tex] are:
[tex]\[ \boxed{-2, -1, 0, 2} \][/tex]
1. Rewrite the equation:
Start with the given polynomial equation:
[tex]\[ x^4 + x^3 = 4x^2 + 4x \][/tex]
2. Bring all terms to one side:
To facilitate solving, we move all terms to one side of the equation:
[tex]\[ x^4 + x^3 - 4x^2 - 4x = 0 \][/tex]
3. Factor the polynomial:
To solve for [tex]\( x \)[/tex], we can try to factor the polynomial. Notice that all terms have a common factor, which is [tex]\( x \)[/tex]:
[tex]\[ x(x^3 + x^2 - 4x - 4) = 0 \][/tex]
This gives us one root directly:
[tex]\[ x = 0 \][/tex]
4. Solve the remaining polynomial:
Now, we need to solve the cubic equation:
[tex]\[ x^3 + x^2 - 4x - 4 = 0 \][/tex]
Through further factoring or using methods such as the Rational Root Theorem, we can find that the factors of this polynomial include [tex]\( (x + 2) \)[/tex], [tex]\( (x + 1) \)[/tex], and [tex]\( (x - 2) \)[/tex].
This means we can write:
[tex]\[ x^3 + x^2 - 4x - 4 = (x + 2)(x + 1)(x - 2) \][/tex]
5. Find the remaining roots:
Solve for [tex]\( x \)[/tex] from the factored form:
[tex]\[ (x + 2) = 0 \quad \Rightarrow \quad x = -2 \][/tex]
[tex]\[ (x + 1) = 0 \quad \Rightarrow \quad x = -1 \][/tex]
[tex]\[ (x - 2) = 0 \quad \Rightarrow \quad x = 2 \][/tex]
6. Collect all roots:
Combining these solutions, we get the roots of the polynomial equation [tex]\( x^4 + x^3 = 4x^2 + 4x \)[/tex]:
[tex]\[ x = -2, -1, 0, 2 \][/tex]
Therefore, the roots of the given equation [tex]\( x^4 + x^3 = 4x^2 + 4x \)[/tex] are:
[tex]\[ \boxed{-2, -1, 0, 2} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.